Twentieth Century Historical Methods in Sri Lanka and S.G. Perera’s: A History of Ceylon for Schools - Portz, Josie (História da Historiografia: International Journal of Theory and History of Historiography, 2025)
Twentieth-century pre-independence Sri Lanka saw the emergence of a new generation of historians that embraced “modern” approaches to writing history. As in other regions of South Asia, these histories were often in service of projects of identity formation. One historian from this group, S.G. Perera, made significant contributions towards knowledge of the history of the Catholic Church in Sri Lanka in particular, translating a significant amount from Portuguese historical materials. As part of a larger project investigating the relationship between historical practice and Catholic identity through the work of Sri Lankan Jesuit historian and priest S.G. Perera, this article focuses on Perera’s 1932 textbook, A History of Ceylon for Schools. Using qualitative coding methods, it observes the historical method and discourse used in Perera’s textbook to demonstrate how he worked within this modern tradition to rhetorically advance a Catholic, Sri Lankan nationalist perspective.